ANALISIS ”RANGKAIAN TAHAPAN OPERASIONAL” PEMBUATAN BELIUNG BATU DARI PERBENGKELAN NEOLITIK DI BANYUWANGI SELATAN - Sofwan Noerwidi (Balai Arkeologi Yogyakarta, 2013)
Prehistoric research in South Banyuwangi by the National Center of Archaeology of Yogyakarta Regional Office between 2008-2011 have found artifact assemblage which indicating stone tool workshop activities. The typology of artifacts which reflecting workshop activities, including; nucleus, percutor, debitage, rough adze, and polishing stone. This paper uses chaîne opératoire approach to reconstruct the producing process and technological aspects related to the manufacturing process of stone adze from neolithic workshop sites in the region. This study is expected to increasing our understanding on technological perspective in the manufacture of Neolithic stone tools, and to give some idea about the social aspects of life of Austronesian speaking people in Indonesia.